ORGANIZATION OF THE GAME «ZARNITSA» IN THE FOOTSTEPS OF THE RED BANNER 28TH ARMY - Samigullina G. S. (University as a factor of Modernization of Russia: History and Prospects (to the 55th anniversary of the I.N. Ulyanov ChSU), 2024)
the article examines the author's participation in the game «Zarnitsa», organized in 1968 by the pioneer and Komsomol organizations of the Yashkul secondary school of the Kalmyk Autonomous Soviet Socialist Republic. A hiking trip in the footsteps of the 28th Army of Khulkhutta-Yashkul is described.
Keywords: Великая Отечественная война; Great Patriotic War; игра «Зарница»; 28 армия; game «Zarnitsa»; 28th Army